THU0712 Dutch norm scores for four dutch-flemish promis item banks important for patients with rheumatoid arthritis. (15th June 2017) - Crins, MH; Roorda, LD; Vet, HC de; Westhovens, R; Boers, M; Dekker, J; Terwee, CB
Abstract : Background: In the assessment of patients with rheumatoid arthritis (RA) it is important to measure physical function, fatigue, pain behavior and pain interference. The Patient-Reported Outcomes Measurement Information System (PROMIS) initiative developed item banks for measuring these concepts. These item banks were translated into Dutch-Flemish language. Objectives: To facilitate interpretation and implementation of PROMIS in the Netherlands, we aimed to calibrate and validate the Dutch-Flemish PROMIS Physical Function (DF-PROMIS-PF), Fatigue (DF-PROMIS-FA), Pain Behavior (DF-PROMISPB) and Pain Interference (DF-PROMIS-PI) Item Banks in the general Dutch population, to obtain Dutch norm scores for these item banks. Methods: 3365 persons of the general Dutch population completed a web-based survey, of which 1309 persons completed the full DF-PROMIS-PF (121 items), 1007 persons completed the full DF-PROMIS-FA (95 items), and 1049 persons completed the full DF-PROMIS-PB (39 items) and the full DF-PROMIS-PI (40 items). The sample was stratified for gender, age, education, and ethnicity according to the distribution of the 2015 census of the general Dutch population. A one-factor confirmatory factor analysis (CFA) was performed per item bank to assess unidimensionality. A graded item response model (GRM) was fitted per item bank to evaluate the item characteristics of the item banks and to facilitate future development of computer adaptive tests (CATs). Ordinal regression models were used to evaluate Differential Item Functioning (DIF) for language (Dutch vs. English) as a measure of cross-cultural validity. Results: All four item banks showed good fit to the GRM: they showed good fit indices for CFA and high percentages of explained variance by first factor. The item banks showed only little local dependency and the scalability coefficients suggested strong scalability for all four item banks. The item characteristics showed good coverage across the range of the four concepts. DIF analyses are in progress. Conclusions: The item banks exhibited good psychometric properties in the general Dutch population. The four Dutch-Flemish PROMIS item banks can be used to develop CATs for measuring physical function, fatigue, pain behavior and pain interference in the Netherlands. Dutch norm scores are presented. Disclosure of Interest: None declared